Self-Healing in Javanese Muslim Community: A Study on Asthma Patient in Surabaya City - Rahmawati, Pudji (Proceedings of International Conference on Da'wa and Communication, 2019)
Asthma is not actually a contagious disease, but this disease is classified as a dangerous disease. Asthma can reduce the quality of life of a person. In fact, it can cause death for sufferers if not handled properly. Every asthma patient has different knowledge and experience in managing and curing asthma. Especially related to illness, illness, and treatment of asthma. This study aims to determine self-healing by asthma patients, the majority of whom come from Javanese ethnicity and are Muslim. Javanese have a philosophy of life including; Nrimo Ing Pandum, Rila, Ngluruk Tanpa Bala Menang Tanpa Ngasorake, and Manunggaling Kawulo Gusti. The research method used is qualitative-phenomenological. Data collection techniques through in-depth interviews, observation, documentation and field notes. The research subjects were patients who treated at the asthma clinic of RSUD dr. Soetomo Surabaya. The results showed that there is a unique self-healing that is carried out by patients with asthma, every things that happens is always accepted and there is a connection with God. Self-healing can help strengthen the emotions (thoughts, attitudes, and actions) of asthma patients. So that in the healing process, patients can be categorized as a fully controlled asthma patient and a partially controlled asthma patient.